Molybdenum oxide and hybride films as anodes for lithium ion batteries - Karahan, Billur Deniz; Yağsı, Ceren; Keleş, Özgül (American Scientific Publishers, 2019)
Scientists have been working to replace graphite, the state-of-art anode material, to improve battery performances. In this sense, transitional metals and their oxides become attractive due to their capacities, widespread availabilities, and environmental benignity. In this paper, first in literature, a progressive study has been followed to evaluate the possible uses of pristine, partially oxidized and reduced Mo oxide films (with glucose droplets on top of the oxide layer gives the hybride and the film without glucose droplets on top of the oxide film gives merely reduced Mo oxide film) as anodes in lithium ion batteries. Unlike to conventional studies, herein the oxidation of molybdenum (Mo) atoms is restricted with the surface atoms to benefit the advantages of metallic Mo atoms at the electrode/current collector interface. These Mo atoms which are inactive versus Li and insoluble in copper are expected to create conductive pathway in the oxide (or hybride) films as well as minimize volume changes in cycling. Knowing that carbonaceous materials have been used as efficient additives to improve the electrochemical performance of electrodes, the best performance is achieved when the hybrid molydenbum oxide (C film on top of the reduced molybdenum oxide film as a result of the reduction of the glucose droplet) sample is cycled between 0.005-3.0 V versus Li/Li+.
WOS: 000448031900047
PubMed ID: 30360177
Keywords: Magnetron Sputtering; Molybdenum Oxides; Hybride Electrode; Anode; Lithium Ion Battery